Arabidopsis PLDz2 Regulates Vesicle Trafficking and Is Required for Auxin Response - Li, G.; Xue, H.W.
Phospholipase D (PLD)and its product, phosphatidic acid (PA), play key roles in cellular processes, including stress and hormonal responses, vesicle trafficking, and cytoskeletal rearrangements. We isolated and functionally characterized Arabidopsis thaliana PLDz2, which is expressed in various tissues and enhanced by auxin. A PLDz2-defective mutant, pldz2, and transgenic plants deficient in PLDz2 were less sensitive to auxin, had reduced root gravitropism, and suppressed auxindependent hypocotyl elongation at 298C, whereas transgenic seedlings overexpressing PLDz2 showed opposite phenotypes, suggesting that PLDz2 positively mediates auxin responses. Studies on the expression of auxin-responsive genes and observation of the b-glucuronidase (GUS)expression in crosses between pldz2 and lines containing DR5-GUS indicated that PLDz2, or PA, stimulated auxin responses. Observations of the membrane-selective dye FM4-64 showed suppressed vesicle trafficking under PLDz2 deficiency or by treatment with 1-butanol, a PLD-specific inhibitor. By contrast, vesicle trafficking was enhanced by PA or PLDz2 overexpression. Analyses of crosses between pldz2 and lines containing PIN-FORMED2 (PIN2)- enhanced green fluorescent protein showed that PLDz2 deficiency had no effect on the localization of PIN2 but blocked the inhibition of brefeldin A on PIN2 cycling. These results suggest that PLDz2 and PA are required for the normal cycling of PIN2- containing vesicles as well as for function in auxin transport and distribution, and hence auxin responses.